PENGEMBANGAN SISTEM INFORMASI PENGELOLAAN KEPESERTAAN DANA PENSIUN DAN PERHITUNGAN MANFAAT PENSIUN - Nurhatin -; Catur swahyudiI; Joko Triyono (Jurnal SCRIPT, 2018)
Dana Pensiun Pembina Potensi Pembangunanin the management of membership data and pension benefit calculation is still manual or still using the help of Microsoft Excel. The use of Microsoft Excel still has shortcomings for the management of membership data pension funds and for the process of calculating the benefits of pensions, thus making the performance that is not maximal. Therefore, in processing the data required a system that can facilitate in the process of data processing membership and pension benefit calculation process. This system is created using PHP programming language. MySQL for database management, Apache as a web server and system design using UML. The existence of a membership management system and the calculation of pension benefits can provide convenience to Dana Pensiun Pembina Potensi Pembangunan in managing membership data, data of heirs, actuarial data, retirement data and data contribution. This system also provides convenience in the process of calculating the retirement benefits that the automatic calculation process when adding data to participants who will retire. In addition to processing the data, this system can also store all data recaps that can be accessed again in the future. The system also provides reports relating to the membership of pension funds, so as to facilitate the board in presenting the report required leadership.